Estudio comparativo sobre zonas pesqueras en el mundo - Oldfelt, Carin (Estudios Internacionales, 1970)
During the last two decades, especially during the 1960s, various nations have extended their rights to fishing grounds. Nowadays, it can be considered an accepted custom for a coastal nation to extend its control over fishing areas beyond the limit of its territorial waters, and as such, this policy has acquired the authority of general rule of International Law. We analyze the different events that have been developing in most of the countries of America, Europe and the Asian countries of the Pacific Basin and that serve as an illustration of this expansive trend.